Comparative Study of Textural Characteristics on Methane Adsorption for Carbon Spheres Produced by CO2 Activation - Wen Yang; Yanyan Feng; Wei Chu (International Journal of Chemical Engineering)
Resorcinol-formaldehyde resin polymer was used as raw material for preparation of carbon spheres. Samples were treated with CO2 flow at 850°C by varying activation times. The CO2 activation granted better pore development of pore structure. The experimental data of CH4 adsorption as a function of equilibrium pressure was fitted by Langmuir and Dubinin-Astakhov (D-A) models. It was concluded that the high surface area and micropore volume of carbon spheres did unequivocally determine methane capacities. In addition, a thermodynamic study of the heat of adsorption of CH4 on the carbon spheres was carried out. Adsorption of CH4 on carbon spheres showed a decrease in the adsorption heat with CH4 occupancy, and the heat of adsorption fell from 20.51 to 12.50 kJ/mol at 298 K and then increased to a little higher values at a very high loading (>0.70), indicating that CH4/CH4 interactions within the adsorption layer became significant.